A parallel-group controlled clinical study to evaluate the efficacy of self-family-environment empowerment diet management intervention in improving outcomes for pregnant women with gestational diabetes mellitus - Jing, Ji; Liu, Yina (Frontiers in Public Health, 2025)
IntroductionGestational diabetes mellitus (GDM) is a serious health problem that poses threats to both mothers and babies, thus leading to the intensive need for management. The current study examined how the SFEE diet management intervention affected glycemic control, maternal outcomes, and dietary compliance in GDM.MethodsPatients not enrolled were ascribed to either the SFEE intervention group or a control group in which standard dietary advice was provided. Although the assessors of the outcome were blind, the participants and providers were not. The principal outcomes included fasting blood glucose, HbA1c, macrosomia, cesarean rates, compliance, and GDM knowledge. Ethical approval was granted by the First Hospital of Shanxi Medical University Ethics Committee (ClinicalTrials.gov registration ID: NCTO6707064).ResultsAll acute and long-term outcomes generally showed that the degree of improvement in fasting glucose and HbA1c was greater in the SFEE group compared with the rest (−0.45 mmol/L, p < 0.01; −0.35%, p < 0.05); 12% with macrosomia in the SFEE group versus 25% in the contrast group (p < 0.05); and cesarean section necessitations 18% in the SFEE group against 30% in the counterpart group (p < 0.05). Concerning other variables, dietary adherence and GDM knowledge also reported higher values (p < 0.05); the adherence proportion here is over 85%, with only a 6.25% dropout rate.ConclusionThe SFEE found that the intervention improved glycemic control, maternal outcomes, and adherence, facilitated by increasing family and social support. This suggests a promising dietary intervention for managing GDM.